Designing instructional materials for teaching surahs and duas for elementary school students in Turkey - Turel, Yalin Kilic; Gulmez, Cigdem; Kavak, Rahime (Ieee, 2013)
There are several types of institutions which provide private Quran instruction in Turkey. The most prevail of institutions are Imam-Hatip High Schools and private Quran courses. Also, after the changes in educational system in 2012, optional Quran courses have been made available to all students in elementary schools. In addition, there is a mandatory course entitled Religious Culture and Moral Education in schools. However, teaching Quran is not a part of course content. Rather, it aims to teach individuals cultural, religious, and moral values. Also, within this course, students are required to learn short surahs and duas for prayer and their Turkish meanings. However, while teaching/learning these surahs and duas, teachers and students face many difficulties. Specifically, students who do not know Arabic have to memorize those surahs and duas that are written by using letters from Latin Alphabet, which causes incorrect readings phonetically. Also, this course is given two hours per week; thus, it is difficult for teachers to focus on each student and correct mis-readings. In this study, based on the problems mentioned above, an instructional material was designed to help students learn short surahs and duas for prayer. Elementary school students' development level and features of interactive whiteboards were considered while designing the software. The software consists of three levels. The first level aims to teach students surahs and duas in Arabic by listening and watching. The second level focuses on their meanings. The third level is devoted for sustainability through practices. Students who get to the third level have to answer some filling-the-gap and drag & drop questions, matching the meanings with surahs/duas, and similar activities.
Taibah-University International Conference on Advances in Information Technology for the Holy Quran and Its Sciences (NOORIC) -- DEC 22-25, 2013 -- Al Madinah, SAUDI ARABIA
Keywords: Technology integration; Holy Quran teaching; instructional material; elementary school students